2017
DOI: 10.1103/physreva.95.033845
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically induced transparency with superradiant and subradiant states

Abstract: We construct the electromagnetically induced transparency (EIT) by dynamically coupling a superradiant state with a subradiant state. The superradiant and subradiant states with enhanced and inhibited decay rates act as the excited and metastable states in EIT, respectively. Their energy difference determined by the distance between the atoms can be measured by the EIT spectra, which renders this method useful in subwavelength metrology. The scheme can also be applied to many atoms in nuclear quantum optics, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…A theoretical group lead by J. Feng [5,6] studied our data as well as all other previous experiments in this area and showed that the evidence strongly disfavors dark photons. They proposed a new theory, however, that synthesizes all existing data and determined that the discovery could indicate a fifth fundamental force [5].…”
Section: Introductionsupporting
confidence: 54%
“…A theoretical group lead by J. Feng [5,6] studied our data as well as all other previous experiments in this area and showed that the evidence strongly disfavors dark photons. They proposed a new theory, however, that synthesizes all existing data and determined that the discovery could indicate a fifth fundamental force [5].…”
Section: Introductionsupporting
confidence: 54%
“…Most work focuses on the low light intensity limit, where interactions between excitations is negligible and the full quantum model simplifies to a problem of classical scatterers. In these models, the collective effects can be exploited, especially when the atoms are arranged periodically on a lattice, leading to effects such as electromagnetically induced transparency interferences [13,14], long-time excitation storage in subradiant modes [15] and enhanced optical cross sections [16].…”
Section: Introductionmentioning
confidence: 99%
“…6). However, it is reported that proper level modulation from Stark shift can induce coherent transfer between |D and |B [28]. Here we take advantage of the in-situ tunability of level spacing of a superconducting qubit.…”
Section: Parametric Drive Induced Mode Transfermentioning
confidence: 99%